Teacher Professionalism Development Planning - et. al., Amilda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to: (1) describe activity planning; (2) describe time planning; (3) describe the planning of funds; (4) describe the program’s sustainability planning. This research uses a qualitative approach used to answer the research focus, namely how to plan teacher professionalism development for activity aspects, time aspects, fund aspects, and program sustainability aspects.